The validity of the mobile gamification in economic subject - Zainal Adnan, Mohd Zaim; Abd Majid, Mohamad Zuber; Mafarja, Nofouz; Wakimin, Nur Fadzlunnisaa’; Mohamad, Maslawati (Institute of Advanced Engineering and Science, 2025)
Mobile gamification has shown growing adoption in education, demonstrating potential to enhance engagement and learning outcomes. This study addresses challenges in economics education, including moderate student achievement, reliance on teachers, and lack of student motivation. To tackle these issues, a mobile gamification tool was developed for secondary school economics. The study’s objective was to validate the content and educational relevance of this tool. Using a sequential exploratory mixed-method design, the research comprised two phases. First, focus group discussions (FGD) were conducted with seven economics and technology experts to assess the tool’s interface and educational content. In the second phase, a content validity index (CVI) assessment quantified expert agreement on five key content areas. Results indicated a high level of expert consensus, with CVI values ranging from 0.87 to 1.00. These findings demonstrate that the gamified mobile tool is a valid educational resource that aligns with curriculum standards and can enhance student engagement in economics. The study concludes that mobile gamification is an effective strategy to support Economics education, encouraging self-directed learning and classroom interaction.